1995
DOI: 10.1104/pp.107.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Low Water Potential Disrupts Carbohydrate Metabolism in Maize (Zea mays L.) Ovaries

Abstract: Water deficit during pollination increases the frequency of kernel abortion in maize (Zea mays 1.). Much of the kernel loss is attributable to lack of current photosynthate, but a large number of kernels fail to develop on water-deficient plants even when assimilate supply is increased. We examined the possibility that assimilate utilization by developing ovaries might be im-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
144
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(159 citation statements)
references
References 24 publications
13
144
1
1
Order By: Relevance
“…In general, Suc levels of stressed ovaries are higher or at least similar to those of non-stressed ovaries (Schussler and Westgate, 1991;Schussler and Westgate, 1995;Zinselmeier et al, 1995), indicating that the capacity to use Suc may be impaired by drought. A central role has also been implicated for hexose to Suc balance in regulating key aspects of ovary and seed development (Weber et al, 1996(Weber et al, , 1998Wobus and Weber, 1999;Weschke et al, 2000).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In general, Suc levels of stressed ovaries are higher or at least similar to those of non-stressed ovaries (Schussler and Westgate, 1991;Schussler and Westgate, 1995;Zinselmeier et al, 1995), indicating that the capacity to use Suc may be impaired by drought. A central role has also been implicated for hexose to Suc balance in regulating key aspects of ovary and seed development (Weber et al, 1996(Weber et al, , 1998Wobus and Weber, 1999;Weschke et al, 2000).…”
mentioning
confidence: 94%
“…Sturm and Tang, 1999). In maize, activity of vacuolar and cell wall-bound acid invertases predominate during ovary and early kernel development, whereas Suc synthase also becomes important during the storage phase of grain-fill (Zinselmeier et al, 1995;Weschke et al, 2000). Drought stress decreases activities of both vacuolar and cell wall-bound acid invertase during kernel development (Zinselmeier et al, 1995), with parallel reductions in ovary growth and concentration of hexoses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gyenesné et al (2002) recorded a close positive correlation between ear yield and the rainfall quantity in July (Hegyi et al, 2005). Long-term water deficiency during flowering increased the frequency of aborted kernels in the ears (Zinselmeier et al, 1995). Quaranta et al (2001) reported that water stress affected flowering, yield quantity and grain quality parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Zinselmeier et al (1995) reported that grain weight was most sensitive to abiotic stress during grain formation which limiting assimilates flow toward developing grain (Lee and Tollenarar, 2007). However, potassium application improved grain weight in this experiment through mitigating adverse effect of high temperature on cell number and size in young ovules and was marked by rapid grain expansion and might be related to the low levels of metabolic activities within developing grain.…”
Section: Economic Analysismentioning
confidence: 99%